Phase transitions in solid Kr-CH4 solutions and rotational excitations in phase II: Classical Cryocrystals - Bagatskii, M.I.; Mashchenko, D.A.; Dudkin, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The heat capacity CP of solid Kr–n CH4 solutions with the CH4 concentrations n = 0.82, 0.86, 0.90 as well as solutions with n = 0.90, 0.95 doped with 0.002 O2 impurity has been investigated under equilibrium vapor pressure over the interval 1–24 K. The (T,n)-phase diagram was refined and the region of two-phase states was determined for Kr–n CH4 solid solutions. The contribution of the rotational subsystem, Crot, to the heat capacity of the solutions has been separated. Analysis of Crot(T) at T < 3 K made it possible to estimate the effective conversion times t and the energy gaps E1 and E2 between the tunnel levels of the A-, T-and A-, E-nuclear-spin species of CH4 molecules in the orientationally ordered subsystem, and to determine the effective energy gaps E1 between the lowest levels of the A- and T- species. The relations t(n) and E1(n) stem from changes of the effective potential field caused as the replacement of CH4 molecules by Kr atoms at sites of the ordered sublattices. The effective gaps EL between a group of tunnel levels of the ground-state libration state and the nearest group of excited levels of the libration state of the ordered CH4 molecules in the solutions with n = 0.90 (EL = 52 K) and 0.95 (EL = 55 K) has been estimated.